Recombinant Rv1654 protein of Mycobacterium tuberculosis induces mitochondria‐mediated apoptosis in macrophage. (24th March 2021) - Lee, Kang‐In; Choi, Seunga; Choi, Han‐Gyu; Gurmessa, Sintayehu Kebede; Dang, Thi Binh; Back, Yong Woo; Park, Hye‐Soo; Kim, Hwa‐Jung
Abstract: Mycobacterium tuberculosis contains diverse immunologically active components. This study investigated the biological function of a newly identified component, Rv1654, with the potential to induce apoptosis in macrophages. Recombinant Rv1654 induced macrophage apoptosis in a caspase‐9/3‐dependent manner through the production of reactive oxygen species (ROS) and interaction with Toll‐like receptor 4. In addition, Rv1654 induced the production of tumor necrosis factor‐α, interleukin‐6, and monocyte chemoattractant protein‐1 through the mitogen‐activated protein kinase pathway. Furthermore, Rv1654‐induced c‐Jun N‐terminal kinase (JNK) activation was inhibited by the ROS scavenger and Rv1654‐induced apoptosis was inhibited by the JNK inhibitor. Moreover, it was found that treatment of macrophages with Rv1654 led to the loss of mitochondrial membrane potential, release of cytochrome c into the cytosol, and translocation of Bax into the mitochondria. Finally, Rv1654‐mediated apoptosis was inhibited in macrophages transfected with Bax siRNA. These results suggest that Rv1654 induces macrophage apoptosis through a mitochondrial‐dependent pathway and ROS‐mediated JNK activation.